2018
DOI: 10.17113/ftb.56.02.18.5450
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fermentation on the Protein Digestibility and Levels of Non-Nutritive Compounds of Pea Protein Concentrate

Abstract: In order to determine the impact of fermentation on protein quality, pea protein concentrate (PPC) was fermented with for 11 h and total phenol and tannin contents, protease inhibitor activity, amino acid composition and protein digestibility were analyzed. Phenol levels, expressed as catechin equivalents (CE), increased on dry mass basis from 2.5 at 0 h to 4.9 mg CE per 1 g of PPC at 11 h. Tannin content rose from 0.14 at 0 h to a maximum of 0.96 mg CE per 1 g of PPC after 5 h, and thereafter declined to 0.79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 17 publications
8
78
2
1
Order By: Relevance
“…Furthermore, sourdough fermentation of chickpea, pea, and kidney bean (Phaseolus vulgaris) (24 h, 30 • C) with L. plantarum V48 and L. brevis AM slightly but significantly reduced the amount of condensed tannins; at the same time, total phenolics were clearly increased, with some exceptions in the kidney bean group [92]. On the other hand, in a study using pea protein concentrate as a fermentation substrate for L. plantarum strain NRRL B4496, total tannin content, along with the total phenolic content, was found to increase; in this study, a fermentation period no longer than 11 h was applied [31]. The authors speculated this phenomenon to result from the liberation of tannin compounds from the lignocellulosic matrix during the fermentation process [31].…”
Section: Fermentation Increases Nutrient Availability In Commonly Concontrasting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, sourdough fermentation of chickpea, pea, and kidney bean (Phaseolus vulgaris) (24 h, 30 • C) with L. plantarum V48 and L. brevis AM slightly but significantly reduced the amount of condensed tannins; at the same time, total phenolics were clearly increased, with some exceptions in the kidney bean group [92]. On the other hand, in a study using pea protein concentrate as a fermentation substrate for L. plantarum strain NRRL B4496, total tannin content, along with the total phenolic content, was found to increase; in this study, a fermentation period no longer than 11 h was applied [31]. The authors speculated this phenomenon to result from the liberation of tannin compounds from the lignocellulosic matrix during the fermentation process [31].…”
Section: Fermentation Increases Nutrient Availability In Commonly Concontrasting
confidence: 59%
“…This effect on protein digestibility may be a general effect for most of the food fermented with LAB and has been reported in different fermented foods, such as sourdough, with sprouted flour and quinoa yogurt-like products after fermentation with Lactobacillus rossiae LB5, Lactobacillus plantarum 1A7, Lactobacillus sanfranciscensis DE9, Lactobacillus rhamnosus SP1, Weissella confusa DSM 20194, and Lactobacillus plantarum T6B10 [26,30]. It is important to consider that fermentation can increase protein digestibility; meanwhile, some bacterial strains can use and reduce the amount of some essential amino acids, reducing the nutritional value of these proteins [31]. Considering the production purposes, if the objective is a beneficial modulation of protein digestibility, it is important to carefully select starter cultures that increase protein digestibility maintaining or increasing the nutritional value, releasing and synthetizing essential amino acids and not consuming them.…”
Section: Fermentation Processmentioning
confidence: 99%
“…The fermented chestnuts with CU and KF5 had positive effects on protein digestibility according to the results of protein digestion ( (Çabuk et al, 2018;Chandra-Hioe, Wong, & Arcot, 2016). This was also confirmed by the increase in amino acids content during fermentation (Table 1).…”
Section: In Vitro Protein Digestibilitysupporting
confidence: 52%
“…Fermentation can inhibit the catalysis of digestive enzymes and promote protein cross‐linking. Protease secreted during fermentation can degrade protein, thus improving the digestibility of protein in vitro (Çabuk et al, ; Chandra‐Hioe, Wong, & Arcot, ). This was also confirmed by the increase in amino acids content during fermentation (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Literature reports various effects of fermentation on proteins in other food matrices. Several studies (Çabuk et al, 2018; Ojokoh, Fayemi, Ocloo, & Nwokolo, 2015) observed an increase in pea and acha rice flour, respectively, while others (Klupsaite et al, 2017; Omowaye-Taiwo et al, 2015) reported a decrease in crude protein content during fermentation of lupine and a melon type, respectively. An increase in crude protein content may be attributed to loss of dry matter (mainly carbohydrates).…”
Section: Resultsmentioning
confidence: 99%